Analisis Sikap Siswa Kelas XI MP (Manajemen Perkantoran) Terhadap Pembelajaran Bahasa Inggris Sebagai Bahasa Asing Di SMKN 1 Bangli - I Wayan setiawan; Luh Made Dwi Wedayanthi; Kadek Dwi Pebriyanti (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to analyze students' attitudes toward learning English at the intermediate level in SMK Negeri 1 Bangli, Indonesia. Employing a qualitative research method, data were gathered through interviews, observations, questionnaires, and documentation from students of class XI MP 1. Data analysis was conducted by applying the content analysis method. The research findings indicate that the majority of students exhibit negative attitudes in cognitive, affective, and conative aspects, characterized by a lack of confidence and interest in learning English. DespiteLuh teachers taking steps to enhance student engagement, such as using varied teaching methods and instructional media, challenges persist regarding student motivation and self-confidence. The implications of this research provide a foundation for developing more effective learning strategies to improve students' attitudes toward learning English at SMK Negeri 1 Bangli.